Human Resource Management Practices and Performance of Small and Medium Enterprises (Smes) in Uganda: A Case of Ntungamo Municipality - Patrick, Atyanga (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate Training in partial Fulfilment of the Requirements for the award of A Master of Arts in Human Resource Management of Kabale University